2014
DOI: 10.12691/ajbr-2-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>Hymenolepis nana</i> in Indigenous Tapirapé Ethnic Group from the Brazilian Amazon

Abstract: A total of 1528 stool samples were examined during a survey of intestinal parasites in 542 members of the Tapirapé ethnic group (279 females and 263 males), who live in the Brazilian Amazon region of Mato Grosso. Overall, 542 individuals from six indigenous villages were enrolled of whom 45 (8.3%) were positive for Hymenolepis nana based on analysis by microscopy of fecal concentrates. H. nana was more prevalent in male individuals (77.8%) as compared to females (22.2%). Moreover, males aged under 15 years hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…Kpoda et al (2015) found in Burkina Faso the eggs of H. nana in water used for irrigation. The absence of a fountain, the lack of hygiene, and the presence of people already infected with H. nana in the concession are factors that contribute to the maintenance of transmission (Mason, 1994;Al-Shammari et al, 2001;Huda Thaher, 2012;Magalhaes Soares et al, 2013;Malheiros et al, 2014). At home overcrowding in concessions is a factor that would increase the risk of contamination of H. nana eggs (Magalhaes Soares et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kpoda et al (2015) found in Burkina Faso the eggs of H. nana in water used for irrigation. The absence of a fountain, the lack of hygiene, and the presence of people already infected with H. nana in the concession are factors that contribute to the maintenance of transmission (Mason, 1994;Al-Shammari et al, 2001;Huda Thaher, 2012;Magalhaes Soares et al, 2013;Malheiros et al, 2014). At home overcrowding in concessions is a factor that would increase the risk of contamination of H. nana eggs (Magalhaes Soares et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Hymenolepis nana is the most prevalent parasite tapeworms (Magalhaes et al, 2013). It is a cosmopolitan parasite by its distribution and it is more prevalent in warm climates (Malheiros et al, 2014). It is endemic in Asia, Africa, Eastern and Southern Europe and Brazil (Huda Thaher, 2012;Malheiros et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, only a few hundred cases have been reported globally; however, prevalence studies have shown rates in excess of 8% in the Brazilian Amazon region of Mato Grosso (Malheiros et al, 2014). The flour beetle, Tribolium castanean is an intermediate host for the tapeworm Hymenolepis diminuta.…”
Section: Transmissionmentioning
confidence: 99%
“…This worm is the only cestode capable of completing its cycle without an intermediate host. Infection is most commonly acquired from eggs in the feces of another infected individual, which are transferred by contamination in food (Malheiros et al 2014). Since ancient times, plants and herbal preparations have been used as medicine.…”
Section: Introductionmentioning
confidence: 99%